Utilizing Essay Punch In Teaching Essay Writing : EFL University Students’ Perception - Fitri Handayani; Mike Amelia (Journal of English Language Learning, 2024)
This study cond The rapid development of technology has brought significant contributions to language teaching. Hence, several up to date writing devices have been used by lecturers to modify teaching and learning activities. This study aims to investigate EFL university students' perception of the use of Essay Punch in teaching essay writing. Essay punch is an online interactive writing tool that provides students guidance in the process of writing step by step in writing an essay. The data were collected through questionnaires administered to the second year English department students of Mahaputra Muhammad Yamin University, Indonesia. The questionnaire was built up into two sections: (1) ten close-ended items and (2) two open-ended items. The ten close-ended items were designed to obtain students’ perceptions on the use of Essay Punch as a writing tool from three different aspects. The aspects are the students’ perception about the device of Essay Punch, the students’ perception about the utility of Essay Punch, and the students’ perception about the affective aspect of Essay Punch in essay writing. Meanwhile, two open-ended questions were put to allow students to show their opinion on the Essay Punch. The findings revealed that EFL university students show a positive view of their experience in using Essay Punch in the writing classroom. Thus, it could be concluded that Essay Punch can become one of the potential tools in teaching essay writing.